THE PROGNOSTIC AND PREDICTIVE VALUE OF KI-67 PROLIFERATION INDEX AND uPA/PAI-1 COMPLEX IN SERUM FOR PATIENTS WITH EARLY INVASIVE BREAST CANCER - Pušina, Sadat; Hodžić, Edin; Salibašić, Mirhan; Bičakčić, Emir; Herenda-Pušina, Naida; Halilović, Emsad (Sanamed, 2024)
Introduction: Breast cancer, the most common malignancy in women, represents a significant health issue, and biomarkers such as the Ki-67 index and uPA/PAI-1 complex can provide insight into treatment outcomes and therapeutic response. Objective: The primary outcome of the study was the assessment of 5-year disease-free survival (DFS), defined as the postoperative period until the occurrence of loco-regional or distant metastases and death from any cause. Patients and Methods: A retrospective cohort study included 166 patients with early invasive breast cancer, in whom the prognostic and predictive significance of the uPA/PAI-1 complex and Ki-67 biomarkers in surgically treated patients at the Clinic for General and Abdominal Surgery of the University Clinical Center in Sarajevo was evaluated during the period from September 2015 to February 2017. Results: Univariate regression analysis identified an increased probability of DFS shorter than five years in patients with negative hormone receptors, positive HER-2 receptor, ≥8 positively mph nodes, and a Ki-67 index ≥14% (p<0.05). Multivariate regression analysis revealed that T2 stage, tumor size of 20-50 mm, and a Ki-67 index ≥14% were associated with a higher probability of DFS shorter than five years (p<0.05). The five-year DFS rate was higher in patients with a Ki-67 index <14% compared to those with ≥14% (p=0.011), while there was no difference in five-year DFS among patients with different levels of the uPA/PAI-1 complex (p=0.636). Conclusion:Our study highlights the importance of the Ki-67 proliferative index as a strong prognostic and predictive factor for DFS in patients operated on for early invasive breast cancer. Additional monitoring and tailored therapeutic strategies may be beneficial in patients with elevated Ki-67 index values, T2 stage, and tumor size of 20-50 mm.